Principles of Program Analysis (1st printing, 1999)

The Corrected 2nd Printing implements the following changes:

Preface

-          new paragraphs added towards the end of the preface

Chapter 1: Introduction

-          section 1.5 modified in a non-trivial manner

-          example 1.7 modified

Chapter 2: Data Flow Analysis

-          subsection 2.1.4 before example 2.10: a new sentence

-          proof of theorem 2.21: two = became \supseteq, Lemma 2.22 -> 2.20

-          proof of lemma 2.32: some \ell -> l

-          section 2.5.1: some dom(\rho) -> dom(\varsigma)

-          example 2.3.7: some \delta' -> \delta

-          before example 2.40: some (\delta) inserted

-          miniproject 2.2 modified in a non-trivial manner as in section 1.5

Chapter 3: Constraint Based Analysis

-          the paragraph after example 3.4 went from du-chains to ud-chains

-          example 3.17 modified towards the end (C(8)->C(9), rho(y)->rho(z))

-          section 3.4.2: Figure 3.7 -> Table 3.7

-          the paragraph before section 3.5 has been rephrased

-          chapter 3 concluding remarks: separation the -> separation of the

Chapter 4: Abstract Interpretation

-          example 4.18: exercise 4.9 -> exercise 4.10

-          example 4.19 towards the end: will include -> will be included in

-          10 lines before example 4.35: rephrasing

-          section 4.5.2: 4 lines before "mundane approach": rephrasing

-          section 4.5.2: after Galois connection: example 4.7 -> example 4.6

-          last lines of proof of proposition 4.44 rephrased

-          miniproject 4.1: explanation of S changed

-          exercise 4.3: theorem 3.7 -> theorem 3.10

Chapter 5: Type and Effect Systems

-          section 5.3.3: breath -> breadth

Chapter 6: Algorithms

Appendix A: Partially Ordered Sets

-          proof of lemma a.8: lemma a.6 -> lemma a.2

Appendix B: Induction and Coinduction

-          appendix B: Banach applies to complete metric space

-          example b.2: some ^\infty now ^\omega; a proof is now made by induction

Appendix C: Graphs and Regular Expressions

References

-          references [7] [54] [109] [130] updated